TANTANGAN INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH BERBASIS PESANTREN DI SMK SULTHON FATTAH - Hikmani Kamila; Siti Hardiyanti; Khoiron Al Abdi; Muhammad Nuzli (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
This study examines the challenges of technology integration in Islamic Religious Education (IRE) learning at a pesantren-based vocational school, focusing on novice IRE teachers at SMK Sulthon Fattah. Technology integration is an essential demand of 21st-century education, including religious education. However, its implementation in pesantren-based schools presents unique characteristics and constraints. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, classroom observations, and documentation involving novice IRE teachers, the school principal, ICT teachers, and students. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The findings indicate that the low level of technology integration in IRE learning is not caused by limited facilities, but rather by insufficient pedagogical digital literacy among novice teachers, school policies restricting students’ smartphone use, the absence of structured professional mentoring programs, and weak collaboration between ICT teachers and IRE teachers. The study emphasizes the importance of a holistic approach that integrates school policies, teacher competency development, and a collaborative school culture to promote effective technology integration in Islamic Religious Education within pesantren-based schools.